2020
DOI: 10.1186/s12915-020-00792-6
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics and genotype-phenotype association analyses reveal conserved genetic architecture of complex traits in cattle and human

Abstract: Background: Lack of comprehensive functional annotations across a wide range of tissues and cell types severely hinders the biological interpretations of phenotypic variation, adaptive evolution, and domestication in livestock. Here we used a combination of comparative epigenomics, genome-wide association study (GWAS), and selection signature analysis, to shed light on potential adaptive evolution in cattle. Results: We cross-mapped 8 histone marks of 1300 samples from human to cattle, covering 178 unique tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 92 publications
1
37
0
Order By: Relevance
“…Further validation using higher coverage genomes is warranted. Lastly, our analysis focused on variants in the coding regions; however, non-coding regions are increasingly known to play important regulatory roles, and some variants within these regions likely have significant biological functions [ 73 ]; future studies should be designed to explore the evolutionary and functional roles of variants within regulatory regions in domestication and genetic improvement of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Further validation using higher coverage genomes is warranted. Lastly, our analysis focused on variants in the coding regions; however, non-coding regions are increasingly known to play important regulatory roles, and some variants within these regions likely have significant biological functions [ 73 ]; future studies should be designed to explore the evolutionary and functional roles of variants within regulatory regions in domestication and genetic improvement of chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fetal adaptive response by affecting insulin metabolism may adversely affect animal feed efficiency. It's worth mentioning that due to the similarities underlying embryonic development in humans www.nature.com/scientificreports/ and cattle and the conserved genetic architecture of complex traits in both species 69 , our findings can help understanding the effects of maternal nutrition on human fetal development. Obesity, molecular disorders, and cardiovascular diseases later in life have been associated with pre-natal maternal stressors 8,70 .…”
Section: Discussionmentioning
confidence: 86%
“…For instance, it has been demonstrated that the immune system mounts a specific autoimmune response against hair follicle antigens [ 53 ], and that the breakdown of the hair follicle immune privilege leads to T-cell inflammation [ 54 ]. These results reveal the importance of integrating omics data for the detection of relevant tissues and candidate genes for complex traits [ 21 , 62 64 ] and suggest the potential of cross-species mapping to benefit the livestock industry and human biomedicine [ 65 , 66 ]. However, it should be noted that the PheWAS results based on human data, similar to the results from comparative genomic mapping, are not easily transposable to findings in livestock, and that their interpretation is often biased by many factors that differ between humans and livestock.…”
Section: Discussionmentioning
confidence: 99%